Partisipasi Mahasiswa Menjelang Pemilihan Kepala Daerah Sumatera Utara Tahun 2024 di Era Digital (Studi di Badan Pengawasan Pemilihan Umum Provinsi Sumatera Utara) - Bondar, Lista Ade Sumiati; Siregar, Hisar (Innovative: Journal Of Social Science Research, 2025)
This research aims to analyze the participation of North Sumatra students ahead of the 2024 Regional Head Election (Pilkada) in the context of the digital era. Students, as a young generation who are technologically literate, have an important role in shaping the future of regional politics. In the digital era, access to information and involvement in the political process is increasingly open through social media and digital technology. Student political participation is strongly influenced by several factors, such as accessibility of information, political education, social environment, and perceptions of candidates. Digital technology and social media provide space for students to access information, discuss and be actively involved in political campaigns, which in turn increases their political awareness. However, various challenges still exist, including low digital literacy, political apathy and information overload. This research concludes that social media and digital technology have a big role in shaping student political participation in the 2024 Pilkada, but their effectiveness is very dependent on digital literacy and adequate access to technology. Efforts to increase student participation in the digital era can be done through political education and interactive campaigns, which are expected to strengthen youth participation in the democratic process in North Sumatra.